Semantic Meaning and Pragmatic Intention in Politeness Strategies: A Pragmatic Analysis of Workplace Communication in The Devil Wears Prada - Taufiq Akbar Nasution; Gracia Vania Maria; Shaila Iqtianty Limbong; Mika Rafael Ketaren; Yohana Afriana Siagian; Zahwa Adelia Damanik; Meisuri Meisuri (Faculty of Tarbiyah nad Teacher Training, 2026)
This research explores the relationship between semantic significance and pragmatic purpose in courteous speech acts depicted in The Devil Wears Prada. Based on Brown and Levinson’s (1987) politeness theory, the study seeks to determine the various politeness strategies employed by the characters and to examine how meaning and intention are formed in hierarchical workplace interactions. Using a qualitative descriptive approach, the data were gathered from chosen conversations in the film that represent different speech acts. These statements were classified into four strategies of politeness: positive politeness, negative politeness, bald-on-record, and off-record. The results indicate that positive politeness is the strategy most commonly employed, highlighting the significance of preserving social connections and unity among characters. Nonetheless, the employment of negative politeness and bald-on-record tactics emphasizes the significant power dynamics and authority inherent in professional environments. Moreover, off-the-record tactics are used to express criticism or implicit meanings without direct confrontation. The examination reveals that the difference between semantic and pragmatic meaning significantly influences communication, especially in conveying power, navigating relationships, and upholding professionalism. This research enhances the comprehension of how politeness tactics operate in media discussions and mirrors genuine communication behaviors in structured settings.